Melt pond ice sampling for nutrients, oxygen isotope compositions, salinity, dissolved organics and bacterial cell abundance during expedition PS122/5 (MOSAiC Leg 5) to the Central Arctic in August-September 2020 - Daiki Nomura; Ryota Akino; Alison L Webb; Yuhong Li; Manuel Dall extquotesingleOsto; Katrin Schmidt; Elise Sayana Droste; Emelia Chamberlain; Nikolai Kolabutin; Egor Shimanchuk; Ruzica Dadic; Allison A Fong; et al. (PANGAEA, 2025)
Nutrient concentrations (NO3-, NO2-, NH4+, PO43-, and Si(OH)4), water oxygen isotope compositions (δ18O), salinity, dissolved organics (TDN and TDP), and bacterial cell abundance were measured for ice samples from melt pond, and water from melt pond and lead during MOSAiC Leg 5 (August and September 2020). Ice cores for the melt pond bottom ice and melt pond surface ice were collected using an ice corer (Mark II coring system, Kovacs Enterprises, Inc., Indianapolis, USA). Also, we sampled small pieces of the pond bottom ice dislodged and floated to the surface of the melt pond by poking with a ruler. After sampling ice samples, we immediately drilled holes on ice and measured ice temperatures with a needle-type temperature sensor (Testo 110 NTC, Brandt Instruments, Inc., USA). Ice cores were segmented at 10-cm intervals. Dislodged ice was cut into 0.25 m exttimes0.25 m size. All ice samples were placed into ice melting bags (Smart bags PA, AAK 5L, GL Sciences Inc., Japan) and melted in the dark at +4°C. For the discrete water sampling from the melt ponds and leads, first, we checked the vertical structure and depth of the meltwater layer from the same hole used for the RINKO Profiler (ASTD152, JFE Advantech, Japan) by attaching a conductivity sensor (Cond 315i, WTW GmbH, Germany) to a 2-m-long ruler and inserting the ruler into the lead water until the salinity measured with the Cond 315i increased at the meltwater–seawater interface. Water was pumped up with a peristaltic pump through a 2-m-long PTFE tube (L/S Pump Tubing, Masterflex, USA) at depths corresponding to meltwater (surface), the interface between meltwater and seawater (interface), and seawater (bottom). Salinity was measured at each depth by attaching a Cond 315i conductivity sensor to the bottom of the ruler. The tube intake was likewise attached to the bottom of the ruler. Ice melt water and water samples from melt pond and lead were subsampled into a 30-mL glass, screw-cap vials for later δ18O analysis, a 100-mL polypropylene bottles for salinity, and into 50-mL polyethylene screw-cap vials (Thermo Fisher Scientific Inc., Waltham, MA, USA) for later measurement of nutrient and dissolved organics concentrations, after filtration through a 0.22-μm Durapore polyvinylidene fluoride membrane filter (MILLEX GV Filter unit, Merck Millipore Ltd., Germany). Samples for δ18O were stored at room temperature (+20°C). Salinity was measured with the same conductivity sensor used for the sea ice (Cond 315i, WTW GmbH, Germany). The samples for nutrient measurements were stored in a freezer (–20°C) before analysis. The samples for flow cytometric analysis were taken in triplicates or quadruplicates of 1.8 mL of sample water and fixed with 36-μL 25% glutaraldehyde (0.5% final concentration) at +4°C in the dark for approximately 2 hours, then flash frozen in liquid nitrogen and stored at -80°C until analysis. Oxygen isotope analyses were carried out with a mass spectrometer (DELTA-S Finnigan MAT, USA) at the ISOLAB Facility at AWI Potsdam by the equilibration method (details in (Meyer et al., 2000, 2022). Nutrient samples were analyzed at the AWI Nutrient Facility between January and March 2021 using a Seal Analytical AA3 continuous flow auto-analyzer, controlled by AACE software version 7.09. Best-practice procedures for the measurement of nutrients were adopted following GO-SHIP recommendations (Becker et al., 2019; Hydes et al., 2010). Bacterial cell abundance was measured using flowcytometry. The abundance of bacteria was determined using a FACS Calibur (Becton Dickinson) flow cytometer with a 15 mW 480 nm (blue) laser. Prior analysis of bacteria, samples were first thawed, diluted x10 and x100 with 0.2 μm filtered TE buffer (Tris 10 mM, EDTA 1 mM, pH 8), stained with a green fluorescent nucleic acid dye (SYBR Green I ; Molecular Probes, Eugene, Oregon, USA) and then incubated for 10 min at 80°C in a water bath (Dominique et al., 1999). Stained samples were counted at a flow rate of around 60 μL min-1 and different groups discriminated on a biparametric plot of green florescence (BL1) vs. side scatter (SSC). For HNF analysis, the samples were stained with SYBR Green I for 2 h in the dark and 1-2 mL were subsequently measured at a flow rate of 500 μl min-1 following the protocol of Zubkov et al. (2007). The abundance of virus and bacteria was determined using a FACS Calibur (Becton Dickinson) flow cytometer with a 15 mW 480 nm (blue) laser. Prior analysis of virus and bacteria, samples were first thawed, diluted x10 and x100 with 0.2 μm filtered TE buffer (Tris 10 mM, EDTA 1 mM, pH 8), stained with a green fluorescent nucleic acid dye (SYBR Green I ; Molecular Probes, Eugene, Oregon, USA) and then incubated for 10 min at 80°C in a water bath (Marie et al., 1999). Stained samples were counted at a flow rate of around 60 μL min-1 and different groups discriminated on a biparametric plot of green florescence (BL1) vs. side scatter (SSC). This allowed to distinguish virus particles of different sizes, and different bacterial groups including low nuclear acid (LNA) and high nuclear acid (HNA) bacteria. Names of size groups of photosynthetic and heterotrophic organisms are in accordance to "Standards and Best Practices For Reporting Flow Cytometry Observations: a technical manual (Version 1.1)" (Neeley et al., 2023).